1989
DOI: 10.1016/0014-5793(89)81091-9
|View full text |Cite
|
Sign up to set email alerts
|

The N‐terminal domain I of human lactotransferrin binds specifically to phytohemagglutinin‐stimulated peripheral blood human lymphocyte receptors

Abstract: Human lactotransferrin receptors have been recently characterized on mitogen-stimulated human lymphocytes [(1989) Eur. J. Biochem. 179, 481-487]. In order to define the lactotransferrin recognition site by these receptors, the binding to lymphocytes of several tryptic fragments, isolated from human lactotransferrin by mild tryptic hydrolysis [(1984) Biochim. Biophys. Acta 787, 90-96]; has been investigated. The 30 kDa N-tryptic fragment (residues 4-281) and the re-associated N,C-tryptic complex bind to lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…N-and C-lobes also possess unique binding regions for microbial membranes [6]. The participation of N-and C-lobes in binding to cell surface receptors has also been reported [5,7,8]. Bovine lactoferrin (bLf) C-lobe is also reported to promote the contractile activity of collagen gels more prominently than native bovine lactoferrin or it's N-lobe [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-and C-lobes also possess unique binding regions for microbial membranes [6]. The participation of N-and C-lobes in binding to cell surface receptors has also been reported [5,7,8]. Bovine lactoferrin (bLf) C-lobe is also reported to promote the contractile activity of collagen gels more prominently than native bovine lactoferrin or it's N-lobe [9].…”
Section: Introductionmentioning
confidence: 99%
“…Each lobe has two domains (N1 and N2, C1 and C2) and can bind a single ferric ion concomitantly with one bicarbonate ion very tightly [2]. There are striking conservation between these two lobes in respect of their iron retention ability (C-lobe bind iron more tightly) [3] and biological functions (some functions of Lf are thought to be involved in the N-lobe) [4,5]. N-and C-lobes also possess unique binding regions for microbial membranes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Lactoferrin binds to cells by at least two mechanisms: 1) high capacity low-affinity binding that may occur via charge-charge interactions with surface glycolipids or other molecules such as DNA (71)(72)(73)(74)(75)(76) and 2) lower capacity/higher affinity binding to one or more proteinaceous plasma membrane receptors (77)(78)(79)(80)(81)(82)(83). Lactoferrin has been reported to bind to B cells via interaction with DNA on the cell surface (74,75) and it appears that B cell binding is mediated through the highly charged N-terminal sequence of lactoferrin (84).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no specific protein receptors for lactoferrin on the B cell surface have been reported. Thus, the biological response to CpG ODN bound to lactoferrin could be different in those cells possessing one or more high-affinity lactoferrin-binding mechanisms such as macrophages, hepatocytes, PHA-activated lymphocytes, and gastrointestinal epithelial cells (77)(78)(79)(80)(81)(82)(83). This requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These sequences have been elucidated to exist on the surface of the protein structure. 23) Rochard et al 24 ) have also reported that the binding site of Lf by the lymphocyte receptor is located at N-terminal domain I (sequence 4-90 and/or 258-281). It is interesting whether the agglutination of bacterial cells by Lf would be correlated with the corresponding sequences of these domains.…”
Section: Effects Of Chemically Modified Proteins On the Agglutinationmentioning
confidence: 99%